IFRS accounting quality in Latin America: A comparison with anglo-saxon and continental European countries and the role of cross-listing in the U.S. - Santana, V.; Rathke, A.; Lourenço, I.; Dalmácio, F. (2014 American Accounting Association's Annual Meeting, 2014)
This study analyses the level of IFRS accounting quality in Latin America, when compared to Anglo-Saxon and Continental European countries. It also analyses the role of crosslisting in the US when comparing the level of accounting quality of Latin American firms with foreign firms. Prior literature has focused on developed countries. There is a lack of knowledge about less developed countries, especially in Latin America, despite their relevant role on the global economy. This paper fills this gap in the literature by analysing the level of IFRS accounting quality in the main Latin American Countries applying IFRS (Brazil and Chile), when compared to the main Anglo-Saxon countries with IFRS tradition (United Kingdom and Australia), but also when compared with the main European Continental economies (France and Germany). The results show that Latin American firms present a lower level of accounting quality, even when only those firms cross-listed in the U.S., regarded as global players, are compared. Thus, even with a unique set of high quality accounting standards (IFRS) and strong reporting incentives, countries’ specific characteristics still play an important role in the way as IFRS are applied.